Insulin regulation of multiple ribonucleic acid species in human skeletal muscle in insulin-sensitive and insulin-resistant subjects - Thompson, D. B. (The journal of clinical endocrinology and metabolism, 1996)
In vivo short term (2 h) insulin-regulated gene expression was examined in skeletal muscle of persons with differing insulin sensitivities. Nine genes were analyzed by a S1 nuclease protection assay with multiple probes (multiple S1 nuclease protection assay) to allow the simultaneous examination of RNA abundances from the multiple genes. In insulin-sensitive individuals, 5 of these 9 genes were insulin responsive. RNA from the proto-oncogenes c-Ha-ras, c-myc, and c-src transiently increased 2- to 4-fold within 30 min of insulin infusion. In addition, the RNA abundance of myf-5, a muscle specific differentiation factor, increased 3-fold with a time course similar to that of c-Ha-ras, c-myc, and c-src. In contrast, type 1 protein phosphatase alpha (PPP1A) RNA levels decreased by 50% within 30 min. In insulin-resistant individuals, the RNA levels of c-Ha-ras and myf-5 did not increase, whereas c-src RNA did increase within 30 min of insulin infusion. RNA encoding c-myc transiently increased in both groups; however, this response was lower in insulin-resistant individuals than in insulin-sensitive individuals in a pattern similar to c-Ha-ras and myf-5. PPP1A RNA levels slightly increased in insulin-resistant individuals. In both insulin-sensitive and insulin-resistant persons, RNA quantities of GLUT4, c-jun, c-fos, and the insulin receptor did not change over the period of insulin infusion. However, overall RNA levels of the insulin receptor and c-jun were lower in insulin-resistant individuals.